Maltrato Psicológico - Granja Paucarima, Cristina Elizabeth (2017)
Child abuse has existed since time ago, when the parents considered that the children were their property and that any way punishment was accepted as normal in society. Over the years and after much research, researchers have determined that the types of punishment are framed within child abuse; one of the ways is psychological abuse, this one affects to children emotionally and cognitively. In Ecuador the statistics made by UNICEF indicate that children and adolescents have been subjected to violent treatment and the Ministerio de Inclusión Económica y Social in its study shows that only a quarter of people psychologically abused denounce the abuses, most of them due to lack of knowledge or fear, thus they decide to keep in silent and continue being psychologically abused with the risk of falling into another type of abuse that can be physical and sexual and finally trigger a social problem. This research study on the psychological abuse applied the methods and the research instruments that allowed to obtain information of the students and teachers of República de Colombia school....